Global comparison of breast cancer burden between women aged 20–54 and ≥55 years (1990–2021) - Ouyang, Xingxin; Liu, Hao; Jin, Huimin (Frontiers in Oncology, 2026)
BackgroundWhile the global burden of breast cancer continues to rise, comparative long-term trends in incidence and mortality between reproductive-age and older women remain inadequately characterized across different socio-demographic settings.MethodsData on female breast cancer incidence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021 were obtained from the Global Burden of Disease 2021 study. Trends were analyzed for two age groups (20–54 and ≥55 years). The Estimated Annual Percentage Change (EAPC) was calculated using joinpoint regression, which identifies significant trend changes by fitting a series of linear segments connected at “joinpoints.”Statistical comparisons of trends between age groups and SDI regions were conducted using t-tests based on the Joinpoint software framework.ResultsBetween 1990 and 2021, global breast cancer incidence increased in both age groups, with a more pronounced rise among women aged 20–54 years. Mortality and DALYs diverged: both increased in younger women but declined in those aged ≥55 years. Geographic disparities were strongly linked to SDI levels; although high-SDI regions reported higher incidence, they also showed steeper recent mortality reductions, highlighting the roles of risk factor profiles and healthcare access.ConclusionThis study offers a novel, age-stratified comparison of global breast cancer burden across SDI regions over three decades. Our findings underscore the necessity of age-specific and resource-stratified strategies for prevention and control to mitigate the growing burden in both younger and older women.